Study of the hearing threshold of dance teachers - Affeld, Cristiane Nehring (2015)
Introduction: High sound pressure levels can cause hearing loss, beginning at high frequencies. Objective: To analyze the hearing thresholds of dance teachers. Methods: This study had a cross-sectional, observational, prospective, and descriptive design. Conventional and high-frequency hearing evaluations were performed with dance teachers and subjects in the control group. Results: In all, 64 individuals were assessed, 32 in the research group and 32 in the control group. Results showed that individuals in the research group had hearing loss at frequencies between 4 and 8 kHz, but no significant difference was found between groups. Frequency analysis showed that individuals in the control group had higher thresholds than individuals in the research group at the frequency of 0.25 kHz. In the control group, men showed higher thresholds than women at the frequency of 9 kHz. Conclusion: A low prevalence of hearing loss was found, with no difference between teachers and subjects fromthe control group. No difference was found for hearing thresholds at high frequencies between groups. Results have been partially affected by sex.